Effect of different levels of Nitrogen,Phosphorus and Potassium on Growth and yield of Cowpea,(Vigna sinensis Savi) variety P.118 - Mohankumar B (Department of Agronomy, College of Horticulture, 1978)
An experiment was conducted at the Instructional Farm, Vellanikkara, during the second crop season of 1977 to study for effect of different levels of nitrogen, phosphorus and potassium on the growth and yield of cowpea, variety P. 118. The experiment was laid out in a 33 confounded factorial design confounding N P2 K and NP2 K2 in replications I and II, respectively. The study revealed that plant height increased with incremental doses of nitrogen. Nitrogen at 20kg/ha level contributed to increased nodulation which in turn favorably increased the grain yield. Phosphorus also had significant positive effect on nodulation. Nitrogen at 20 kg/ha and phosphorus at 40 kg P2O5 /ha exerted significant positive influence on the total dry matter production of the crop at harvest. Through their increased response in terms of number of pods per plant, number of seeds per pod and length of pods, nitrogen, at 20 kg ha and P2O5 at 40 kg/ha increased the grain yield per hectare significantly. Application of nitrogen at 30 kg/ha registered the maximum haulm yield. The grain haulm ratio was maximum for the combination of 20 kg nitrogen and 40 kg P2O5/ha Nitrogen at 21.6 kg/ha was found to be the optimum level for maximum grain production. The optimum level of phosphorus could not be estimated since the crop exhibited a linear response beyond the maximum level tried. Nitrogen application increased the plant content as well as the grain content of the element. Similarly application of phosphorus and potassium increased the plant contents of phosphorus and potassium, respectively. The uptake by nitrogen and phosphorus was significantly influenced by the 20 kg/ha and 40kg P2O5 /ha The protein content of grain increased with increasing levels of nitrogen. Applied potassium did not exhibit any significant influence on the yield components and most of the growth attributes.